THE ANALISIS PENGARUH PENILAIAN KESEHATAN BANK MELALUI KOMPONEN RGEC TERHADAP NILAI PERUSAHAAN BANK UMUM SYARIAH DI INDONESIA YANG DIMODERASI OLEH DANA PIHAK KETIGA - Siskiya Febrin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
A healthy bank offers a great advantage that the bank can gain the trust of its customers. The purpose of this study is to determine the health effect of Islamic commercial banks through the RGEC component on firm value with third party funds as a moderating variable. Applying quantitative research methods with data analysis techniques in the form of Partial Least Square. The population of this study is Islamic commercial banks, which were registered in Indonesia from 2016 to 2020. The sample was obtained based on the purposive sampling method, with a total sample of 12 BUS. The results of this study indicate that bank soundness has a significant influence on firm value as evidenced by a P-Value score of 0.000 and a T-Statistic of 4.071. Meanwhile, third party funds have no significant effect on firm value with a P-Value of 0.868 and a T-Statistic of 0.167. The results of the calculation of the moderating effect show a P-Value of 0.935 and a T-Statistic of 0.082, indicating that this study failed to prove that third party funds were able to strengthen the bank's health relationship to the firm value of Islamic commercial banks.